Venous thrombosis and multiple prothrombotic gene defects - Mengis, C.; Biasiutti, F. Demarmels (Hämostaseologie, 2003)
We describe the case of a 30-year-old woman with homozygous prothrombin G20210A transition and heterozygous FV Leiden mutation and a history of postpartum venous thrombosis. Despite the high thrombotic risk to be assumed in the presence of this combined thrombophilia our patient suffered her first venous thrombotic event only at the age of 29 years during the puerperium of her first pregnancy. This fact supports the concept of venous thrombosis as a multicausal disease, with interaction of genetic and acquired risk factors. The case presented also stresses the importance of performing complete thrombophilia investigation.
Keywords: Thrombophilia; venous thromboembolism; FV Leiden mutation; prothrombin G20210A transition